Two new compounds, Talaromycin A and B, isolated from an endophytic fungus, Talaromyces aurantiacus. Issue 19 (1st October 2020) - Zhang, Yi-Fei; Yang, Zhong-Duo; Yang, Xing; Yang, Li-Jun; Yao, Xiao-Jun; Shu, Zong-Mei
Abstract: Two new compounds Talaromycin A (1 ) and Talaromycin B (2 ) were isolated from a liquid culture of Talaromyces aurantiacus. The structures of 1 and 2 were elucidated by IR, MS, 1D and 2D NMR spectra and comparison of the experimental and calculated electronic circular dichroism spectra. Additional known compounds (3–6 ) were also isolated. These compounds were tested for monoamine oxidase, acetylcholinesterase and PI3K inhibitory activity, but showed only weak activity. Graphical Abstract: